CHI '14 Extended Abstracts on Human Factors in Computing Systems 2014
DOI: 10.1145/2559206.2559971
|View full text |Cite
|
Sign up to set email alerts
|

HCI interventions with nonprofit organizations

Abstract: Thirty HCI practitioners participated in a CHI 2011 workshop [7], intending to directly engage with the processes, goals, and challenges of six Vancouver area nonprofit organizations. Analysis of the workshop documentation allowed us to track instances of reciprocal interaction between stakeholders. Findings revealed that various design tactics were productive in enabling collaborators to improve their focus on addressing key challenges in the 2-day workshop. This case study contributes new knowledge -tactics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 7 publications
(5 reference statements)
0
7
0
Order By: Relevance
“…Researchers have argued that the 'sustainability' of individual ICTs must be considered within the 'ecology of devices' within which they are connected [2,3], and within the wider context of practices which constrain an individual's potential interactions [7,19,65,97]. SHCI work has further contended that the route to affecting more sustainable practices is through affecting the even wider 'political ecology', comprised of institutions, infrastructures and cultural norms [43,25,52,57,63,69,73,84]. This category of SHCI contribution is characterized by ethnographic investigations of situated practice, and by critique/agenda setting papers that argue for the need to develop solutions that affect systems-level change.…”
Section: Systems Thinkingmentioning
confidence: 99%
“…Researchers have argued that the 'sustainability' of individual ICTs must be considered within the 'ecology of devices' within which they are connected [2,3], and within the wider context of practices which constrain an individual's potential interactions [7,19,65,97]. SHCI work has further contended that the route to affecting more sustainable practices is through affecting the even wider 'political ecology', comprised of institutions, infrastructures and cultural norms [43,25,52,57,63,69,73,84]. This category of SHCI contribution is characterized by ethnographic investigations of situated practice, and by critique/agenda setting papers that argue for the need to develop solutions that affect systems-level change.…”
Section: Systems Thinkingmentioning
confidence: 99%
“…In the design of a mobile app to support homeless youth in California, researchers engaged initially with subject matter experts and service providers through interviews to inform a prototype, before conducting workshops with young people experiencing homelessness to determine the fnal design [64]. This approach of engaging with service providers and support networks in the frst instance enables their expertise to inform considered engagement with the prospective end user [55]. It helps researchers understand the complexity of the end user's life beyond the aspect that is the focus of the research, thus ensuring engagement is premised upon respect and trust [71].…”
Section: Designing With Marginalised Cohortsmentioning
confidence: 99%
“…Moulder et al highlight the importance of optimising participant time, particularly when conducting HCI with non-proft organisations who are often time-constrained [55]. They propose that it is not useful to engage participants in extended ideation, but to instead use 'advising tactics' to present a consolidated perspective of the problem to participants, alongside options to address the issue.…”
Section: Designing With Marginalised Cohortsmentioning
confidence: 99%
“…Other research has shown potential methods to task multidisciplinary teams of policy experts, visualizers and community members to process quantitative data cooperatively in order to effectively enable community action [67]. The results of this 'Analysis' ideally are straightforward outcomes that are communicated in easy to share formats with all stakeholders [40].…”
Section: Addressing the Challengesmentioning
confidence: 99%